Out-of-school time STEM program: Students’ attitudes toward and career interests in mathematics and science - Guan Saw; Brendan Swagerty; Shon Brewington; Chi-Ning Chang; Ryan Culbertson (International Journal of Evaluation and Research in Education (IJERE), 2019)
Internationally, out-of-school time (OST) science, technology, engineering, and mathematics (STEM) programs abound. However, rigorous evidence of their impacts on student outcomes is scarce. This study evaluated the relationships between OST STEM program participation and student motivational factors in math and science by analyzing survey and administrative data of 1.017 middle school students who participated in the seven-week, STEM-focused Prefreshman Engineering Program (PREP) in San Antonio, Texas, from 2015 to 2017. Multiple regression results indicated that the PREP participation was positively associated with students’ attitudes toward math and interests in math-related careers, whereas the effects on students’ attitudes toward science and career interests in science were negligible. No evidence was found to suggest that the associations between PREP participation and student motivational factors in math and science differed by gender, race/ethnicity, or socioeconomic status.